Energy consumption and battery sizing for different types of electric bus service. (15th January 2022) - Basma, Hussein; Mansour, Charbel; Haddad, Marc; Nemer, Maroun; Stabat, Pascal
Abstract: With the deployment of battery electric buses (BEB) increasing worldwide, proper battery sizing becomes more critical for operators as it dictates bus driving range and costs. In this paper, we present a battery sizing framework based on comprehensive energy needs assessment for BEB. The bus operating conditions are first defined for different types of bus service (City, intercity, shuttle, regional, rapid-transit). Then, BEB energy consumption is evaluated using a comprehensive energy model developed by the authors. Finally, the required battery size is estimated for different types of charging infrastructure. Modeling results show that BEB energy consumption is sensitive to bus service type, ranging widely between 2 and 4.6 kWh/km, and that intercity buses require the largest battery size (320–680 kWh). A practical finding for operators from our Paris case study is that city bus batteries are unnecessarily oversized to accommodate a typically small fraction of trips in rare extreme cold weather conditions. Highlights: Study proposes a battery sizing framework for electric buses. Evaluates energy consumption and battery sizing for different types of bus service. Tool to estimate the required battery size and charging infrastructures. Bus energy consumption and battery size are sensitive to its transit service type. City bus Batteries oversized to accommodate small number of trips during the year.